Explaining the Low Enrollment Intention at International Universities in Indonesia: A Serial Mediation Study - Pranakusuma Sudhana; Noermijati; Ananda Sabil Hussein; Nur Khusniyah Indrawati (Athens Institute for Education and Research, 2023)
This paper aims to explain the unsuccessful relationship between the awareness of prominent international education brands and enrollment intention. A serial mediation model encompassing perceived congruity and brand attitude was developed and was tested using the Partial Least Square-Structural Equation Modeling (PLS-SEM) technique involving 132 respondents. The results revealed that the brand awareness must be subsequently perceived as internally congruent with the prospective students' self-image in terms of resource sufficiency before developing enrollment intention by forming the desired brand attitude. The originality of this study is that it could be the first to discuss the international universities landscape in Indonesia. In addition, the proposed model could be a plausible framework for explaining the intention to accept not only international education brands but also other brands of goods and services, hence benefiting both educational and consumer research. This paper includes generalizability as its limitation with suggestions to undertake the broader scope of studies.